2008
DOI: 10.1007/s11262-008-0293-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced discrimination of African swine fever virus isolates through nucleotide sequencing of the p54, p72, and pB602L (CVR) genes

Abstract: Complete sequencing of p54-gene from 67 European, American, and West and East African Swine Fever virus (ASFV) isolates revealed that West African and European ASFV isolates classified within the predominant Genotype I according to partial sequencing of p72 were discriminated into four major sub-types on the basis of their p54 sequences. This highlighted the value of p54 gene sequencing as an additional, intermediate-resolution, molecular epidemiological tool for typing of ASFV viruses. We further evaluated p5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
256
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(263 citation statements)
references
References 25 publications
5
256
1
1
Order By: Relevance
“…For molecular epidemiological analysis, DNA was extracted from cell cultures and three separate polymerase chain reactions (PCRs) were set up; for p72 genotyping classification amplifying the Cterminal region of p72 protein using the primers p72-U/D as previously described (Bastos et al, 2003) for p54 genotyping amplifying the complete gene encoding the p54 protein using the primers PPA722/PPA89 (Gallardo et al, 2009); for CVR sub-typing using the primer pairs ORF9L-F/9L-R to amplify the CVR located in the B602L gene (Nix et al, 2006). Amplicons of the expected size were excised, purified by Quiaex gel extraction (QIAGEN) and cloned into a pGEMT-Easy vector (Promega) according the manufacturer's instructions.…”
Section: Genomic Amplification and Nucleotide Sequencingmentioning
confidence: 99%
See 2 more Smart Citations
“…For molecular epidemiological analysis, DNA was extracted from cell cultures and three separate polymerase chain reactions (PCRs) were set up; for p72 genotyping classification amplifying the Cterminal region of p72 protein using the primers p72-U/D as previously described (Bastos et al, 2003) for p54 genotyping amplifying the complete gene encoding the p54 protein using the primers PPA722/PPA89 (Gallardo et al, 2009); for CVR sub-typing using the primer pairs ORF9L-F/9L-R to amplify the CVR located in the B602L gene (Nix et al, 2006). Amplicons of the expected size were excised, purified by Quiaex gel extraction (QIAGEN) and cloned into a pGEMT-Easy vector (Promega) according the manufacturer's instructions.…”
Section: Genomic Amplification and Nucleotide Sequencingmentioning
confidence: 99%
“…Recent studies have demonstrated the value of p54-gene sequencing as an additional, intermediate-reso-lution, molecular epidemiological tool for typing of ASFV viruses (Gallardo et al, 2009). Amplification of the fragment containing the complete p54-gene from all the Ugandan isolates produced PCR products of 550 bp, which were identical in sequence.…”
Section: Asf Molecular Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Intensive efforts have been made in the use of genetic epidemiology to analyse the ASF viruses circulating in different parts of Africa in order to gain an significant understanding of the relation between and geographic spread of each circulating genotype (Bastos et al, 2003;Bastos et al, 2004;Lubisi et al, 2005;Boshoff et al, 2007;Lubisi et al, 2007;Gallardo et al, 2009;Owolodun et al, 2010;Gallardo et al, 2011). However, the causes/factors that support the continued circulation of ASF viruses in pig herds in various parts of Africa in general and in Nigerian pig populations in particular remain poorly understood or at best hypothetical.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst alternative genes with greater intra-genotypic resolution capabilities than p72 have been identified [11,19], these alternative genome targets are of limited use for geographically and temporally constrained viruses such as those causing outbreaks in Kenya from 2006-7 [19]. Indeed, for the three genome regions compared in the Kenyan study, only the CVR recovered more than one virus variant [19], and it therefore remains the genome target of choice when attempting to determine the origin and map the spread of closely related virus. It was for this reason that, following genotype confirmation by p72 gene characterisation, that the CVR was used to investigate ASF outbreaks occurring between 2003 and 2006 in the main pig producing areas of Nigeria ( Fig.…”
Section: Introductionmentioning
confidence: 99%